Hukum Islam di Persimpangan: Menjawab Tantangan Bioetika dan Kecerdasan Artifisial - Bobby Ferly; Salma Salma; Muchlis Bahar (Pusat Riset dan Inovasi Nasional, 2025)
Islamic law faces significant challenges from the rapid advancements in bioethics and artificial intelligence (AI). The current responsive approach, based on ad-hoc fatwas, is deemed inadequate to address the systemic ethical dilemmas posed by these disruptive technologies. This research aims to propose a proactive and systematic ijtihad framework capable of anticipating and guiding technological innovation to align with the higher objectives of Shari'ah (Maqasid al-Shari'ah). Using a qualitative, library-based method with a juridical-normative and philosophical approach, this study analyzes primary and secondary Islamic legal sources through the Maqasid al-Shari'ah theoretical framework. The research finds the current model to be limited and, as a solution, offers a novelty in the form of the Hierarchical Model of Technological Ijtihad (HI-Tech). This model is a structured, interdisciplinary reasoning process, supported by a proposed institution, the Bio-Artificial Ijtihad Council (MIBA), and a digital platform,